STUDENTS’ FIGURATIVE LANGUAGE IN CREATIVE WRITING: A STUDY ON EFL WRITING IN STATE UNIVERSITY OF GORONTALO - Jefriyanto Saud; Rini Jayanti Harja (SEAQIL Journal of Language Education, 2023)
Abstract   This research investigates the tendency of English Department students to employ figurative language in creative writing. The study also delves into the generic structure of such language, aiming to understand the nuances within the creative writing produced by the students. Recognizing creative writing as a vital tool for comprehending language characteristics and fostering creativity, this research seeks to address students' challenges in composition arising from a lack of understanding and assumptions about its similarity to conventional writing. A preliminary study revealing insufficient creativity among English Department students in producing figurative language (Juliandini, 2013), this research adopts semantic analysis (Jackson, 2000) as the theoretical framework. Employing a qualitative method, the study analyzes creative writing from eight students. Componential analysis is employed to explore the deep structure of words, unraveling semantic interrelations between components to reveal meanings at the surface level. The results indicate a propensity among students to generate figurative language, with metaphor emerging most frequently in participants' creative writing. Simile, personification, and the less frequent hyperbole follow in occurrence. These findings contribute valuable insights into the creative writing abilities of English Department students, informing strategies to enhance their language proficiency and creative expression. The research underscores the significance of mastering creative writing skills as a means to enrich language capabilities and foster creativity among students.